(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
This study aims at making a link between the investigations of the wood industry on the control of the quality in forest (production of wood adapted to the industrial requirements) and the studies on the wood heat treatment to improve the wood durability and dimensional stability. Heat treatment was carried out under nitrogen at 220 °C. A set of 14 samples (250x110x25 mm) from 7 European oak (Quercus petraea) trees of various French origins were scanned at dry state by X-ray tomography before and after heat treatment for analyzing the effects of treatment on the variation of wood density within and between the samples. The moisture uptake test also was performed and the equilibrium moisture content rates were calculated. The results showed to the naked eye the evident dark color of samples with differences between samples treated at 230 °C and 220 °C; no color differences within samples of heartwood, but differences between heartwood and sapwood. The density values of all samples decreased after the treatment. Mass loss (ML) ranged from 11,27 % to 13,28 % and was major when density was initially high. The treatment had no significant modification on the homogeneity of the density, but the near portion of sapwood was affected. The effects of wood density on the results of heat treatment were the same within samples of same tree but when comparing different trees the trend was highly variable. In conclusion, studying the effects of wood initial density variability on the heat treatment process needs further analysis such as chemical and biological analysis along with X-ray tomography and needs to be carried out on several species.